Metode Ilmiah Sebagai Cara Mendapatkan Pengetahuan dalam Epistemologi - kafara, Muhamad Ridwan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The philosophy of knowledge or epistemology in its development became the history of human thought which became the central theme. The development of philosophy of knowledge or epistemology is indeed concerned with questions about knowledge concerning how to obtain knowledge: What are the sources of a science and knowledge?. To answer the question of whether humans already know with their knowledge, epistemology is the answer. The development of science means the starting point for the study of science based on the principles of in-depth methods and procedures to obtain the truth. In this case, what is meant is the scientific method. Methods are broadly divided into two groups, namely the empirical cycle of natural sciences, and linear methods for social sciences - humanities. The scientific method is a procedure or way to obtain knowledge which is known as science. Not all knowledge can be called because science is a way of getting it must go through and meet certain conditions that must be met so that something called science is obtained through the scientific method.